A digital signal processor for Doppler radar sensing of vital signs - Lohman, B.; Boric-Lubecke, O.; Lubecke, V.M.; Ong, P.W.; Sondhi, M.M. (IEEE engineering in medicine and biology magazine, 2002)
A signal processor for the determination of respiration and heart rates in Doppler radar measurements is described. The processor can reliably calculate both rates for a subject at distances as large as 2 m. The rate determination is based on autocorrelation and uses several enhancement techniques, including a center clipper. Several representative results are included to show the future potential of using the processor for this purpose. Calculated heart rates agree for over 88% of the time with the reference rate, within a 2% margin, for all datasets. These results indicate excellent prospects for remote monitoring of vital signs through noncontact radar techniques.